Pardeh Khani as Performance: An Approach Based on Erika Fischer-Lichte’s Theories - Rahmat Amini; Zahra Shirvani Saadatabadi (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
Pardeh Khani is a distinctive form of traditional storytelling in Iran that is recognized for its unique performative qualities. This performance method combines storytelling, painting, and acting, which has resulted in the formation of a unique style of Iranian painting known as coffeehouse painting. This article examines the characteristics of Pardeh Khani based on performance theory, particularly using Erika Fischer-Lichte’s theories, which emphasizes four key aspects: mediality, materiality, semioticity, and aestheticity, to uncover the performative possibilities of this tradition. Although Pardeh Khani has faced a decline in recent decades, the initial findings of this research indicate that it has the potential for renewal as an interdisciplinary art form by integrating advancements in both painting and narration. Therefore, a comprehensive understanding of its performative possibilities is required to preserve and modernize this performance art.